Add value for graduates with digital credentials. Issue 2 (May 2017) - Hope, Joan
Abstract : Proud graduates take photos with their diplomas. Then they sometimes get the credentials framed to hang on the wall, or sometimes they put them in a filing cabinet. But graduates could do more with their diplomas and certificates if they were in digital format.